Sensitivity to ALA-PDT of cell lines with different nitric oxide production and resistance to NO cytotoxicity - Di Venosa, Gabriela Mariana (2005)
In this work, we studied the in vitro interactions between aminolevulinic acid (ALA)-mediated photodynamic therapy (PDT) and nitric oxide (NO), as well as the interactions between ALA, porphyrins and some NO donors and precursors. We employed three murine adenocarcinoma cell lines: LM2, which does not produce NO; LM3, which produces NO, and LM3-SNP, a variant of LM3 resistant to NO producing the same amount of NO as the parental. We did not find cross-resistance between NO-induced cytotoxicity and ALA-PDT. In spite of the lower porphyrin synthesis, LM2 cells show the highest sensitivity to ALA-PDT. However, we hypothesised that this is not related to the lack of endogenous NO production, because modulation of NO levels did not modify the response to PDT in any of the cell lines. Two unexpected results were found: the enhancement of NO production from the donor sodium nitroprusside (SNP) induced by ALA in both cells and medium, and the inhibition by ALA of NO production from arginine. We also found that SNP strongly protected the cells from ALA-PDT by impairing porphyrin biosynthesis as a consequence of an inhibition of the enzyme ALA dehydratase. We were not able to evaluate the action of NO derived from SNP because of the unexpected porphyrin impairment. On the other hand, impairment of NO from Arginine driven by ALA, although not modulating in vitro the ALA-PDT response, by increasing in vivo blood flow, may be contributing to the mechanism of tumour cures.